Correlation between factors associated with the removable partial dentures use and Candida spp. in saliva - Rocha Gusmao, Joao Milton; Ferreira dos Santos, Silvana Soleo; Neisser, Maximiliano Piero; Cardoso Jorge, Antonio Olavo [UNESP]; Faria, Ivan (Wiley-Blackwell, 2011)
Objectives: To correlate the presence and number of Candida spp. in the saliva of wearers of removable partial dentures retained with precision attachments with the proportion of metal/acrylic resin present in the dentures. Methods: Saliva samples from 40 removable partial denture wearers (test) and one paired sample of individuals, non- wearers of any type of removable denture (control) were collected, seeded, and the colony forming units of Candida counted and identified. The metal/acrylic resin proportion of each denture was quantified, using silicone plates pressed over each denture. Results: Candida spp. was found in the saliva of 80% of the individuals in the test group and 65% of the control, with C. albicans being themost prevalent species. The test group presented with the highest number of colony forming units of Candida per ml of saliva, and there wasweak correlation between this number and the metal and resin area of the denture (Pearson's coefficient of correlation). Greater prevalence and a higher number of colony forming units of Candida per ml of saliva occurred in removable partial denture wearers ( p = 0.04) with a weak positive correlation between the metal and resin area and the number of colony forming units of Candida per ml of saliva. However, this correlation was more significant for the area of resin. Correlation between factors associated with the removable partial dentures use and Candida spp. in saliva
Keywords: acrylic resin; Candida; partial denture